The Quality of Mathematics Education Technology Literature - Robert N. Ronau; Christopher R. Rakes; Sarah B. Bush; Shannon O. Driskell; Margaret L. Niess; David Pugalee (The Evaluation Center at Western Michigan University, 2015)
Background: The present study evaluated the quality of 1,165 scholarly literature papers about mathematics education technology literature. Purpose: The purpose of the present study was to determine the extent to which mathematics education technology literature reports the information needed to support the scientific basis of a study. Setting: N/A Intervention: N/A Research Design: A systematic review was used to organize the data collection and analysis processes   Data Collection and Analysis: A literature search was conducted to identify scholarly papers that addressed the use of technology in mathematics education. A coding process was developed to record descriptive information about each paper. The Quality Framework developed for this process provided a structure to identify key information across research types based on types of analyses conducted, assigning a certain number of possible points based on the type of research conducted. Findings: Dissertations accounted for a surprisingly high portion of the literature and research: 39.7% of the available literature and 57.0% of the research studies. The overall quality of the mathematics education technology literature was lower than we expected, averaging only 48.9% of the points possible. We noted that the quality of research papers, with respect to possible point values averaged 54.6% over four decades. For mathematics education technology researchers, manuscript reviewers, and editors, these results suggest that more attention is needed on the information being included and excluded from scholarly papers, especially with regard to connections to theoretical frameworks and research designs.